Raltegravir in HIV-1 infection: Safety and Efficacy in Treatment-naïve Patients - Pandey, Krishan K. (2011)
The hunt for a compound which inhibits the HIV-1 integrase had been painstakingly difficult. Integrase is essential for viral replication as it mediates the integration of the viral DNA genome into the host DNA resulting in the establishment of the permanent provirus. Persistent efforts have resulted in the discovery of Raltegravir (Isentress, MK-0518), the first integrase inhibitor approved by US Food and Drug Administration for the treatment in HIV-1 infected patients. Numerous clinical studies with raltegravir have found it to be safe and effective in treatment naïve as well as treatment experienced patients. Adverse events associated with raltegravir based therapy are milder compared to previously available regimens. Raltegravir is metabolized primarily via glucuronidation mediated by uridine diphosphate glucuronosyltransferase and has a favorable pharmacokinetics independent of age, gender, race, food, and drug-drug interactions. Within a short period of time of its introduction, raltegravir has been included as one of DHHS recommended preferred regimen for the treatment of HIV-1 infection in treatment naïve patients.